2010
DOI: 10.1101/lm.1546110
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory and the hippocampus: A test of the hippocampal contribution to recollection and familiarity

Abstract: It has been suggested that the hippocampus selectively supports recollection and that adjacent cortex in the medial temporal lobe can support familiarity. Alternatively, it has been suggested that the hippocampus supports both recollection and familiarity. We tested these suggestions by assessing the performance of patients with hippocampal lesions on recognition memory tests that differ in the extent to which recollection and familiarity contribute to the recognition decision. When targets and foils are highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…In that study, the slope of the ROC was greater than 1, even when overall memory performance was very good (e.g., d袌 暇 2). Jeneson et al (2010) suggested that the lure distribution may have equal or greater variance than the target distribution under these conditions because the lures are associated with both recall-to-reject (when the incorrect detail is recollected, adding to high-confidence correct rejections when recollection is strong) and recall-to-accept (when the incorrect detail is not noticed but other thoughts about the item are recollected, adding to high-confidence false alarms when recollection is strong). This would have the effect of increasing the variance of the lure distribution relative to the target distribution, for which only a recall-to-accept process would apply.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the slope of the ROC was greater than 1, even when overall memory performance was very good (e.g., d袌 暇 2). Jeneson et al (2010) suggested that the lure distribution may have equal or greater variance than the target distribution under these conditions because the lures are associated with both recall-to-reject (when the incorrect detail is recollected, adding to high-confidence correct rejections when recollection is strong) and recall-to-accept (when the incorrect detail is not noticed but other thoughts about the item are recollected, adding to high-confidence false alarms when recollection is strong). This would have the effect of increasing the variance of the lure distribution relative to the target distribution, for which only a recall-to-accept process would apply.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas many studies report a disproportionate effect of hippocampal damage on recollection and associative memory relative to familiarity (Huppert and Piercy 1978;VarghaKhadem et al 1997;Holdstock et al 2002;Yonelinas et al 2002;Giovanello et al 2003;Mayes et al 2004;Aggleton et al 2005), other reports find that hippocampal damage impacts familiarity and recollection to a similar extent (Manns and Squire 1999;Stark et al 2002;Manns et al 2003;Cipolotti et al 2006;Wais et al 2006;Jeneson et al 2010;Kirwan et al 2010;Song et al 2011). Interestingly, a patient with significant perirhinal damage that spared the hippocampus showed impaired familiarity and preserved recollection (Bowles et al 2007).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…Functional MTL accounts have prominently focused on psychologically distinct processes underlying recognition memory, i.e., recollection and familiarity: PRC is thought to support familiarity and a PHC-HC network is thought to support recollection (Eichenbaum et al, 2007;Yonelinas et al, 2010). However, Squire and colleagues propose a more unified account of MTL memory processes Wixted and Squire, 2011), in which HC as well as PRC may support both processes, and, in HC patient studies, report memory and learning deficits across processes (Jeneson et al, 2010) and stimulus content (Shrager et al, 2007;Kim et al, 2011). In a recent neuroanatomy-based approach (Wixted and Squire, 2011), they suggested that MTL subregions may process different attributes of memory (see also Squire et al, 2007).…”
Section: Implications For Functional Mtl Modelsmentioning
confidence: 99%